Pembuatan Website Company Profile untuk UMKM Zero Printing di Blitar - Doni Diaraga Rudita; Becik Gati Anjari; Umi Khabibah (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
UMKM Zero Printing is a convection business specializing in screen printing services and t-shirt production in Blitar City. Before having a website, this micro, small, and medium enterprises only relied on Instagram social media as its main promotional media as its media; however, it only had limited features and unoptimum, unstructured information. Related to that, this study aimed to design and build a company profile website based on CMS Wordpress as a digital solution to increase the effectiveness of information consistency and strengthen bussiness image. This study used the Action Research method which includes three main dimensions: Usability, Information Quality, and Interaction Quality. The data were collected through observation, interviews, and distributing questionnaires to ten respondents consisting of business owners, marketing expert teams, computer expert teams, and consumers. The result of the study showed that the domain zeroprintingsupply.com website created obtained an average score that was categorized as very good with a Usability percentage of 84,6%, Information Quality 83,3%, and Interaction Quality 90.6%. This website has been proven to help UMKM in conveying information faster and more professionally, increasing online visibility, and expanding market reach digitally. It can be concluded that the use of a company profile website is able to convey business information more neatly, increase credibility, expand the reach of digital promotions, and provide convenience for consumers in accessing services. This study showed that the implementation of digital media the implementation of digital media through a website is a strategic step in supporting the sustainable digital transformation of UMKM